AN ANALYSIS OF CASES OF DRUG-INDUCED LIVER INJURY REPORTED TO AN ADVERSE DRUG REACTION MONITORING CENTER - SUBRAMANIAM, BALA; SHAH, MEGHA; DESAI, CHETNA; PANCHAL, JIGAR; SHAH, SAMIDH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Drug-induced liver injury (DILI) is a frequent cause of liver injury and acute liver failure .We aimed to analyze the cases of DILI reported over a period of 8 years to the adverse drug reaction (ADR) monitoring center (AMC) at our institution. Methods: This observational retrospective study was conducted at the ADR monitoring center of a tertiary care hospital. Cases reported to the AMC, Pharmacovigilance Programme of India during the year 2011–2018 were analyzed as per the criteria used to analyze the ADRs. Results: A total of 5448 ADRs were reported during the study period, of which 105 (2%) were suspected to be DILI. The mean age of the patients with DILI was 39.26 years. Men (66.66%) were more commonly affected than women (33.34%). The most common drug groups causing DILI were antiretroviral (ART) (42.85%) and antitubercular (ATT) (40%). Most common single drug responsible for DILI was isoniazid (44.44%) followed by atazanavir (28%) and pyrazinamide (22.22%). Increase in serum bilirubin was the most common DILI (64.75%). About 79% of cases had a possible causality and 21% of cases had probable causal association with the suspected drugs. Majority of the ADRs (83%) were not preventable and mild in severity (21%). All ADR forms were complete in accordance with National Coordinating Center scale. Conclusion: DILI is commonly observed in patients taking ART and ATT drugs for more than a month. Regular monitoring and assessment in these patients may help in preventing DILI and manage these ADRs.